Mortality among displaced former UNITA members and their families in Angola: a retrospective cluster survey. Issue 7416 (18th September 2003) - Grein, Thomas; Checchi, Francesco; Escribè, Josep M; Tamrat, Abiy; Karunakara, Unni; Stokes, Christopher; Brown, Vincent; Legros, Dominique
Abstract: Objective To measure retrospectively mortality among a previously inaccessible population of former UNITA members and their families displaced within Angola, before and after their arrival in resettlement camps after ceasefire of 4 April 2002. Design Three stage cluster sampling for interviews. Recall period for mortality assessment was from 21 June 2001 to 15-31 August 2002. Setting Eleven resettlement camps over four provinces of Angola (Bié, Cuando Cubango, Huila, and Malange) housing 149 000 former UNITA members and their families. Participants 900 consenting family heads of households, or most senior household members, corresponding to an intended sample size of 4500 individuals. Main outcome measures Crude mortality and proportional mortality, overall and by period (monthly, and before and after arrival in camps). Results Final sample included 6599 people. The 390 deaths reported during the recall period corresponded to an average crude mortality of 1.5/10 000/day (95% confidence interval 1.3 to 1.8), and, among children under 5 years old, to 4.1/10 000/day (3.3 to 5.2). Monthly crude mortality rose gradually to a peak in March 2002 and remained above emergency thresholds thereafter. Malnutrition was the leading cause of death (34%), followed by fever or malaria (24%) and war or violence (18%). Most war victims and people who had disappeared were women and children. Conclusions This population of displaced Angolans experienced global and child mortality greatly in excess of normal levels, both before and after the 2002 ceasefire. Malnutrition deaths reflect the extent of the food crisis affecting this population. Timely humanitarian assistance must be made available to all populations in such conflicts.